Efekty napływu bezpośrednich inwestycji zagranicznych do Polski - wybrane zagadnienia - Jaworek, Małgorzata; Kuzel, Marcin (The Effects of Foreign Direct Investment Inflows to Poland - Some Selected Issues, 2007)
Foreign capital inflows in the form of foreign direct investment (FDI) to a host country are results of investment decisions made by international corporations (especially by transnational corporations). The effects of these decisions relate not only to starting and running foreign affiliates of transnational corporations but also have an impact on companies in a host country. The paper does concentrate on FDI effects in Poland. It deals with problems involving inter alia fostering linkages between Polish affiliates of the world's largest transnational corporations and domestic companies, the role of such linkages in knowledge and skill diffusion as well as the state-owned enterprises privatization process. The discussion is based on empirical findings which have been obtained by the authors as the results of two independent research projects completion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 237-251